Perceived Coach-Created Motivational Climates as Predictors of Athletes’ Goal Reengagement: The Mediational Role of Goal Motives - Martínez-González, Natalia; Atienza, Francisco L.; Tomás, Inés; Balaguer, Isabel (Frontiers in Psychology, 2021)
Athletes have to face several challenges during the sport season, and one of them could involve dealing with unattainable goals. In these situations, being able to reengage in other goals as a form of goal adjustment and in response to contextual demands is adaptive. According to previous literature, some aspects of the athletes’ social context, such as coach-created motivational climates, could encourage more adaptive responses in athletes, and so it is possible that these climates would also promote athletes’ goal regulation and goal reengagement. The purpose of this study was twofold: to analyze whether athletes’ perception of empowering and disempowering climates were related to their goal reengagement through the mediation of goal motives; and to examine the interaction between the two climates when they predict reengagement through athletes’ goal motives. Participants were 414 Spanish university athletes (49.5% male, 50.5% female) who belonged to different university teams, with ages ranging from 17 to 33 years old (M = 20.61, SD = 2.58). In the sport facilities, all of them completed questionnaires that evaluated their perception of empowering and disempowering climates, their goal motives, and their goal reengagement. SEM results showed that perceived empowering climate positively predicted autonomous goal motives, which in turn had a positive relationship with goal reengagement. Conversely, perceived disempowering climate positively predicted controlled goal motives, which were not related to goal reengagement. Thus, we only found support for the indirect relationship between perceived empowering climate and goal reengagement through autonomous goal motives. Moderated mediation analyses revealed that interaction effects between perceived empowering and disempowering climates were not significant in the prediction of goal reengagement through goal motives. Findings revealed that the perception of empowering climates promotes athletes’ goal reengagement when goals become unattainable via the increase in their autonomous goal motives. Conversely, when athletes perceive disempowering climates, they have more controlled goal motives, which are not related to goal reengagement. In addition, the study supports the need to educate coaches to create more empowering and less disempowering climates.